ENHANCED THE ROLE OF YOUTH IN PARTICIPATING THE SUCCESS OF GREEN ECONOMIC PRACTICES: BEHAVIORAL PERSPECTIVE BASED MODEL - Maria, Maya; Ginting, Ginta; Akbara, Anisa Zahwa; Ngarbingan, Hubertina Karolina (AIBPM Publisher, 2023)
Indonesia has a population of 270 million people and will face tough challenges in obtaining Sustainable Development Goals, especially related to Responsible Consumption and Production (RCP). The Indonesian government created a National Action Plan to achieve sustainable consumption and production patterns, namely increasing economic welfare, reducing resource use, and improving quality of life. To accelerate the call for RCP, encouraging the role of the younger generation to participate in implementing the best of green economic practices is the right strategy. This research is intended to get an overview of the extent to which the younger generation wants to participate from a behavioral angle (green economy consumers). Respondents involved in the study were 229 young people from various regions in Indonesia. Interesting results were obtained from the research model, indicating that intention strongly influences behavior and impacts willingness to participate using the SEM-Lisrel analysis. However, the awakening of intentions among the younger generation is mostly influenced by positive attitudes, while the norms and perceptions do not show strong indications of their influence. These findings form a strong basis for the development of behavioral research that can answer the research gap involving the younger generation to act as green consumers in a proven way. The younger generation can be environmentally responsible consumers by using eco-friendly products.